A study on the information transfer between stock market in South Asia (Thailand, Malaysia, Philippines) / Mohd Raqib Abu Bakar - Abu Bakar, Mohd Raqib (Faculty of Business and Management, 2009)
The relationship between the stock markets of the developed countries has been examined extensively in the literature. This study tries to investigate the information transfer between stock market in south Asia by using three countries (Malaysia, Thailand and Philippines). The Vector Autoregression (VAR) model was applied to five year daily price of stock index from these countries from 2004 to 2008. The result shows that the both dometic relationship and information transfer are existing in Malaysia, Thailand and Philippines. In addition, the study shows that all the three countries have positive relationship between market Malaysia, Thailand and Philippines. There are no interdependencies price relationship between market Philippines and Thailand. There are existed lead-lag relationships between market participants such as investor and regulators in making better investment decisions and policy to control the market.